2014
DOI: 10.1155/2014/613971
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Microendoscopic Resection of the Transverse Process for Treatment of Low Back Pain with Bertolotti’s Syndrome

Abstract: Bertolotti's syndrome is characterized by anomalous enlargement of the transverse process of the most caudal lumbar segment, causing chronic and persistent low back pain or sciatica. We describe the case of a 45-year-old woman who presented with left sciatic pain and low back pain due to a recurrent lumbar disc herniation at L4-5 with Bertolotti's syndrome. Selective L5 nerve root block and local injection of lidocaine into the articulation between the transverse process and sacral ala temporarily relieved the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
0
16
0
2
Order By: Relevance
“…Twenty patients were diagnosed with a bilateral LSTV [ 11 – 20 ]: 10 patients treated bilaterally 8 patients received steroid injections [ 12 , 13 , 20 ] 1 patient treated with resection of the LSTV on both sides [ 16 ] 1 patient surgically treated with lateral posterior fusion [ 18 ] 10 patients treated unilaterally 5 reported only unilateral LBP [ 13 , 15 , 17 ] 4 showed unilateral bony spurs [ 11 , 18 , 19 ] 1 accepted only treatment in the most symptomatic side of LBP [ 16 ]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty patients were diagnosed with a bilateral LSTV [ 11 – 20 ]: 10 patients treated bilaterally 8 patients received steroid injections [ 12 , 13 , 20 ] 1 patient treated with resection of the LSTV on both sides [ 16 ] 1 patient surgically treated with lateral posterior fusion [ 18 ] 10 patients treated unilaterally 5 reported only unilateral LBP [ 13 , 15 , 17 ] 4 showed unilateral bony spurs [ 11 , 18 , 19 ] 1 accepted only treatment in the most symptomatic side of LBP [ 16 ]. …”
Section: Resultsmentioning
confidence: 99%
“…10 patients treated unilaterally 5 reported only unilateral LBP [ 13 , 15 , 17 ] 4 showed unilateral bony spurs [ 11 , 18 , 19 ] 1 accepted only treatment in the most symptomatic side of LBP [ 16 ]. …”
Section: Resultsmentioning
confidence: 99%
“…And the authors pointed out that the results with posterolateral fusion were only slightly better than those with conservative treatment in a comparable group. Whereas, many authors reported favorable results of technique to simply resect the pseudo-articulation or decompress entrapment of the L5 nerve root [6][7][8]13,[24][25][26] . Some of them reported minimal invasive technique using a tubular retractor and suggested that it was recommended as an effective procedure.…”
Section: Operative Techniquementioning
confidence: 99%
“…Current operative techniques for treating BS are normally based on the procedure including decompression of L5 nerve root as well as resection of the pseudo-articulations or the part of TP which contact with ala of sacrum. In recent years, minimally invasive techniques have been reported by a large number of authors [6][7][8][9] . However, there are still only a few reports on percutaneous full endoscopic surgery for BS.…”
Section: Introductionmentioning
confidence: 99%
“…LSTVs include sacralization of the L5 vertebral body and lumbarization of the S1 segment while demonstrating varying morphology, ranging from broadened transverse processes to complete fusion. 5 The most common types of LSTV that present with symptomatic Bertolotti's syndrome are the Castellvi type I and type II; type III and type IV variants rarely present with symptoms referable with confirmatory and provocative testing to the transitional vertebra itself, and therefore there is limited experience and no case reports of treatment toward this particular entity. Case Description We illustrated a case of a 37 years old female in which a computed tomography scan demonstrated type III LSTV on the left and a type I anomaly on the right.…”
mentioning
confidence: 99%